Glial fibrillary acidic protein in plasma and intraocular fluids and the correlation with cognitive function in patients with vitreoretinal disease - Steven Ness; Konstantina Sampani; Fatima Tuz-Zahra; Nurgul Aytan; Sreevardhan Alluri; Marissa G. Fiorello; Xuejing Chen; Nicole H. Siegel; Michael L. Alosco; Weiming Xia; Yorghos Tripodis; Thor D. Stein; et al. (Scientific Reports)
Abstract Ocular imaging and fluid protein levels are emerging as biomarkers for neurodegenerative disease. Elevated levels of plasma glial fibrillary acidic protein (GFAP), a marker of astrogliosis, have been demonstrated early in the course of Alzheimer’s Disease. In this study, we measured GFAP levels in the aqueous and vitreous humors and plasma of 79 participants undergoing vitrectomy surgery for retinal disease and correlated them with subject Mini Mental Status Exam (MMSE) and Trail Making Test part b (TMT-b) scores. Measured GFAP concentrations were higher in vitreous and aqueous than in plasma. Levels of GFAP within the aqueous and vitreous were correlated (r = 0.6; p < 0.0001); however, there was no association between GFAP levels in either ocular fluid and plasma. There was no significant correlation between GFAP levels in any of the measured ocular fluids and cognition as measured by MMSE and TMT-b scores. In plasma, higher GFAP levels were associated with lower TMT-b, but not MMSE, scores. Given that elevated GFAP levels are associated with a variety of vitreoretinal diseases, future studies evaluating its use as a potential biomarker for dementias should concentrate on recruiting subjects without a history of ocular disease.